High thrombus platelet content is associated with a lower rate of first pass effect in stroke treated by endovascular therapy. (December 2022) - Delvoye, François; Di Meglio, Lucas; Consoli, Arturo; Nomenjanahary, Mialitiana Solo; Dupont, Sébastien; Labreuche, Julien; Maier, Benjamin; Piotin, Michel; Blanc, Raphael; Escalard, Simon; Boursin, Perrine; Hamdani, Mylène; et al.
Background and purpose: First pass effect (FPE), the occurrence of complete reperfusion after one pass with no rescue attempt during endovascular therapy (EVT), is associated with the best clinical outcome after an acute ischemic stroke (AIS). Previous studies evaluating FPE occurrence according to EVT technical strategies, occlusion locations, or thrombus composition have provided controversial results. Here, we performed a correlation analysis between FPE occurrence and AIS thrombus cellular composition, as assessed using quantitative biochemical assays. Patients and methods: Homogenates of AIS thrombi from 250 patients were prepared by mechanical grinding. Platelet, red blood cell (RBC), and leukocyte contents of AIS thrombi were respectively estimated by quantification of GP (glycoprotein) VI, heme, and DNA in thrombus homogenates. FPE was defined as a modified Thrombolysis in Cerebral Infraction (mTICI) score of 2C or 3 after a single EVT device pass. Results: AIS thrombi successfully removed after a single pass were poorer in GPVI (0.098 ± 0.023 vs 0.111 ± 0.024 ng/mg, p  < 0.001) compared to those whose removal had required several passes. GPVI content was also significantly associated with a higher number of device passes and a longer procedure time. No such significant correlation was found with DNA and heme content. Discussion and conclusion: Thrombus platelet content may hamper thrombus removal by EVT. This result suggests that adjunctive therapies or functionalization of retrieval devices targeting platelets may improve EVT efficacy.